FINANCIAL PERFORMANCE EVALUATION THROUGH RATIO ANALYSIS: A STUDY ON RURAL POWER COMPANY LTD. - Uddin, Muhammad Salah; Alam, Md. Faisal-E-; Kader, Sheikh Abdul; Imran, Md. Ali; Beg, Tahrima Haque (International Journal of Business and Management Future, 2022)
Financial statements are a set of reports that detail an organization’s cash flows, financial position, and financial results. Financial statement analysis provides a piece of information on the financial status and the present situation of the company as well as able to forecast their future plan. This study makes an effort to evaluate Rural Power Company Ltd.’s financial performance from 2018 to 2020. The present study is mainly based on secondary data collected from the sample unit and results are interpreted in tabular form and bar chart using MS Excel. The results show how effectively the company is managed in terms of production, administration, and sales. It means the economic condition of firm is good. On the other hand, the Current Ratio, Liquid ratio, Debt Equity Ratio, Gross Profit Ratio, Net Profit Ratio, and EPS Ratio are acceptable. But the Return on Equity (ROE) Ratio is not satisfactory, which needs further improvement. An economist can assess the degree of economic power concentration and potential dangers in the financial policies adopted by examining the financial accounts of various firms. The analysis also serves as the foundation for a number of governmental acts concerning licensing, restrictions, price fixing, profit caps, dividend freezes, tax subsidies, and other concessions to the business sector. JEL Classification Codes: I2, L25, M4.